Self-managed abortion as a humanitarian revolution: accounts of a telehealth pilot in the Middle East - Laureline Lasserre; Nelly Staderini; Maysa’a Hasan; Vanessa Rossi (Conflict and Health, 2025)
Abstract Background Access to safe abortion care (SAC) should be improved in fragile and humanitarian settings, and the implementation of interventions in that regard are currently limited. This is especially true for self-managed abortion (SMA), although it holds the potential of revolutionizing the prevention of maternal death and suffering. Case presentation The medical humanitarian organization Doctors Without Borders/Médecins Sans Frontières (MSF) piloted a self-managed abortion model of care in the Middle East. 22 women were remotely supported in managing their safe abortions with a counsellor over the phone, using misoprostol doses that they took at home after having taken mifepristone in our health facility. We share our experience by describing the model of care and discussing the lessons learned through its implementation. Conclusions The program delivered abortion services successfully and required few resources. This paper also reflects on the importance of facilitating SMA in humanitarian contexts. It increases access to care by providing increased confidentiality, close support, ample information, autonomy, and flexibility. It is simple to implement, effective, often preferred by women, and can be linked to information about contraception. The implementation of self-managed models should be expanded, notably in projects that do not have a sexual and reproductive health focus and in restrictive and challenging contexts. It represents a true revolution for access to safe abortion care.